Case Report: Neurological adverse events in subject with myasthenia gravis after PCSK9 inhibitor administration - Adámková, Věra; Vitásková, Martina; Hubáček, Jaroslav A. (Frontiers in Cardiovascular Medicine, 2024)
Background: Myasthenia gravis is a rare chronic autoimmune neuromuscular disorder mainly caused by autoantibodies to the nicotinic acetylcholine receptor. Cholesterol is an essential molecule that affects the distribution and proper functioning of this receptor.Several reports have described the potential worsening of myasthenia gravis in patients treated with statins.The patient was an obese 72 years old man, past smoker, diagnosed with ischaemic heart disease, type 2 diabetes mellitus and lipid metabolism disorder.Statin treatment was not implemented because of chronic myasthenia gravis and PCSK9i monotherapy (Repatha [evolucamab], 140 mg) was implemented to treat dyslipidaemia. Within 24 hours after the first dose of PCSK9i the patient developed severe muscle weakness, joint pain, fever, and general discomfort, lasting for several days. Despite strong advice against the second dose administration, this was self-administered approximately 2 weeks later, leading to report significant worsening of the muscle problems, leading to the patient admittion to the neurology department where he was being treated for myasthenia gravis attack.Based on the neurologist's conclusion, it can be assumed that in this case, treatment with PCSK9i resulted in significant worsening of the patient's chronic disease.